SL-07 Competency of Diploid Parthenogenesis Embryonic Stem Cell (pESC) for Cell Therapy - Arief Boediono (Media Veteriner, 2015)
Naturally, mammalian embryo resulting from the fertilized oocytes by sperm and develops to the zygote with diploid chromosome. Through the embryo engineering, mammalian embryo also could be produce by: nuclear transfer and parthenogenesis. Embryo produce by nuclear transfer method could develop to term with very limited results. However, parthenogenetic embryos could not develop to term because of the incorrect expression of imprinted genes (genomic imprinting).........